Assessment of improvement in functional outcomes between a novel knee replacement design and conventional designs in 240 patients: a randomized controlled trial - Tero Irmola; Aleksi Reito; Jarmo Kangas; Antti Eskelinen; Mika Niemeläinen; Ville M Mattila; Teemu Moilanen (Acta Orthopaedica)
Background and purpose: The introduction and development of new total knee arthroplasty (TKA) implant designs are industry driven. To date, an adequately powered randomized controlled trial (RCT) to provide evidence of the superiority of novel implant designs over conventional ones is often lacking. The aim of our RCT was to investigate the functional outcomes of a novel TKA implant design compared with 2 conventional TKA designs. Primary outcome was difference in the change in Oxford Knee Score (OKS) at 2 years. Secondary outcomes were Forgotten Joint Score, 15D quality of life questionnaire, UCLA activity score, and complications. Methods: We compared functional outcomes between a novel TKA implant design (Persona CR) and 2 conventional designs (NexGen CR, PFC CR). 240 patients with severe knee osteoarthritis were recruited to a pragmatic, single-center, prospective, parallel-group RCT between September 2015 and August 2018. The duration of follow-up was 2 years. Results: Of 240 randomized patients, 225 were included in the intention-to-treat analysis (mean age 61.8 years; 67.5% females). The OKS exceeded minimal clinical important difference (MCID) from baseline to 2 years in all 3 treatment groups (Persona CR: 18.9 points, PFC CR: 20.3 points, NexGen CR: 19.4 points). At 2 years the difference between Persona CR and PFC CR in the change score was –1.0 (95% confidence interval [CI] –3.6 to 1.7). Similarly, the difference between Persona CR and NexGen CR was –0.9 (CI –3.6 to 1.9). At the time of final follow-up evaluation, OKS was equivalent between groups, as CI excluded between-group differences larger than 4 points. Conclusion: We showed no clinically relevant differences in functional outcomes measured with OKS, 15D, or FJS between the 2 conventional implant designs and the novel implant design at 2-year follow-up.